2014
DOI: 10.1111/are.12644
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carbohydrate-to-lipid ratio in diets supplemented withBacillus subtilisprobiotic strain on growth performance, body composition and digestibility in juvenile white seabass (Atractoscion nobilis,Ayres 1860)

Abstract: This study aimed to evaluate the effect of increasing the carbohydrate to lipid ratio in diets supplemented with Bacillus subtilis in white seabass (Atractoscion nobilis) juveniles on digestibility, growth performance, feed utilization efficiency and tissue composition. Four experimental isoenergetic and isoproteic diets supplemented with B. subtilis were formulated with increasing starch to lipid ratios (g/g) of 10:19; 14:17; 18:15 and 22:13 (diets PD10, PD14, PD18 and PD22 respectively). A negative control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…In the current study, the dietary supply of Lacto cel-con significantly enhanced the growth and feed efficiency of tilapia in terms of (weight gain, specific growth rate, condition factor, feed conversion ratio, protein efficiency ratio and net protein utilization) compared to those feded without Lacto cel-con diets. Similar results were detected in tilapia Oreochromis niloticus diet supplemented with Lacto cel-con by (El Zayat, 2014 andHussein et al, 2016) and other type of probiotic (Khattab et al,2004, EL-Haroun et al,2006, Eid and Mohamed, 2008, Olmos et al, 2011, Chiu and Liu, 2014, Ridha and Azad, 2016, Lopez et al, 2016, Dawood et al, 2016b, Dawood et al, 2016c, Dawood et al, 2017and Nguyen et al, 2019.…”
Section: Discussionsupporting
confidence: 75%
“…In the current study, the dietary supply of Lacto cel-con significantly enhanced the growth and feed efficiency of tilapia in terms of (weight gain, specific growth rate, condition factor, feed conversion ratio, protein efficiency ratio and net protein utilization) compared to those feded without Lacto cel-con diets. Similar results were detected in tilapia Oreochromis niloticus diet supplemented with Lacto cel-con by (El Zayat, 2014 andHussein et al, 2016) and other type of probiotic (Khattab et al,2004, EL-Haroun et al,2006, Eid and Mohamed, 2008, Olmos et al, 2011, Chiu and Liu, 2014, Ridha and Azad, 2016, Lopez et al, 2016, Dawood et al, 2016b, Dawood et al, 2016c, Dawood et al, 2017and Nguyen et al, 2019.…”
Section: Discussionsupporting
confidence: 75%
“…Higher lipid content in the diet, which cannot be fully utilized by grouper and tended to cause lipid deposition in different tissues, whereas the amount of lipid content obtained from carbohydrate was probably quite limited. This result confirms a positive correlation between lipid deposition in fish and the lipid content of the diet [ 28 , 38 , 39 ]. As we all know, the levels of triglycerides, cholesterol, glucose and total protein in blood are generally correlated with animal health and indicate the metabolic and physiological state of the organism, and too high or too low in blood will cause aberrant changes in the body [ 40 ].…”
Section: Discussionsupporting
confidence: 78%
“…In this study, the increase in the dietary dextrin level resulted in a significant increase in lipid deposition in whole‐body and muscle tissues and a concomitant increase in HSI and VSI, due to higher dietary energy utilization, both at the digestible and metabolic level. Similarly, several studies reported that dietary digestible energy content, both from lipids or carbohydrates, might modulate lipid accumulation in different tissues (López et al., 2016). There was a positive correlation between dietary lipid levels and whole‐body and liver lipid content in orange‐spotted grouper and other fish species (Li, Wang, Liu, Jiang, & Zhu, 2013; López et al., 2016; Tan, Xie, Zhu, Lei, & Yang, 2007; Zhang et al., 2016; Zhou et al., 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, several studies reported that dietary digestible energy content, both from lipids or carbohydrates, might modulate lipid accumulation in different tissues (López et al., 2016). There was a positive correlation between dietary lipid levels and whole‐body and liver lipid content in orange‐spotted grouper and other fish species (Li, Wang, Liu, Jiang, & Zhu, 2013; López et al., 2016; Tan, Xie, Zhu, Lei, & Yang, 2007; Zhang et al., 2016; Zhou et al., 2016). Also, a positive correlation between dietary carbohydrate level and tissue lipid content was previously reported (Kedar Nath Mohanta, Mohanty, Jena, Sahu, & Patro, 2009).…”
Section: Discussionmentioning
confidence: 93%